Pelaksanaan Rumah Mampu Biaya (RMB) menggunakan instrumen wakaf: Analisis kajian di negeri Johor - Fifi Anti Mapika Sari, Sukamto (2024)
Waqf is not only focused on the medium of welfare and spirituality to the community but also provides solutions to the people's problems such as the issue of affordable housing (RMB). This study aims to identify the factors of RMB insufficiency in the State of Johor and explore the extent of RMB implementation in the State of Johor.In addition, study the RMB method by using waqf instruments and then prepare the RMB model using waqf instruments. To achieve these objectives, an explanatory qualitative study was conducted in two phases. The first phase focuses on the collection of secondary data that is analyzed through qualitative content analysis methods. The second phase focused on the collection of primary data through the instrument of indepth interview sessions involving 13 informants. The interview information was analyzed by qualitative content analysis using ATLAS.ti software version 9.0. The findings shown that the hybrid waqf housing model is very suitable. This is because it is influenced by governance factors involving human resource factors, land position factors and several other factors that are challenges in implementing development methods using waqf. To overcome the problem, several strategies have been put forward including the application of contemporary methods, land redevelopment module waqf, applying the concept of blue ocean strategy and the application of the Islamic-based service marketing triangle model to ensure that appropriate methods of financing the development of waqf land can be implemented in developing waqf land. This study is expected to give a large and positive impact to the RMB developers, academics, endowment management and the general public who are Muslims in elevating and dignifying the concept of " Baldatun Tayyibatun wa Rabbun Ghafur' and the Islamic wealth distribution system.